2017
DOI: 10.1155/2017/3279061
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Antioxidants on Neuronal Dysfunction and Plasticity in Huntington’s Disease

Abstract: Huntington's disease (HD) is characterised by movement disorders, cognitive impairments, and psychiatric problems. The abnormal generation of reactive oxygen species and the resulting oxidative stress-induced mitochondrial damage in neurons upon CAG mutations in the HTT gene have been hypothesized as the contributing factors of neurodegeneration in HD. The potential use of antioxidants against free radical toxicity has been an emerging field in the management of ageing and many neurodegenerative disorders. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 188 publications
(214 reference statements)
0
33
0
2
Order By: Relevance
“…Overall, preintervention, detailed interviews elaborated by the nutritionist (Appendix 2, Supporting Information) revealed that patients had a low‐to‐moderate intake of macronutrients, thus coinciding with a 1989 study that reported a low fat and carbohydrates intake in HD‐patients . After an exhaustive review of guidelines and literature, the nutritionist followed the recommendation of 25–35 kcal kg –1 d –1 , deciding against the high calorie intake frequently recommended (3500–5000 kcal d –1 ), and including essential bioactive compounds . On that basis, a customized diet was designed for each participant, and adherence to these recommendations was high, with the exception of participant number 11, who was diagnosed with anorexia nervosa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, preintervention, detailed interviews elaborated by the nutritionist (Appendix 2, Supporting Information) revealed that patients had a low‐to‐moderate intake of macronutrients, thus coinciding with a 1989 study that reported a low fat and carbohydrates intake in HD‐patients . After an exhaustive review of guidelines and literature, the nutritionist followed the recommendation of 25–35 kcal kg –1 d –1 , deciding against the high calorie intake frequently recommended (3500–5000 kcal d –1 ), and including essential bioactive compounds . On that basis, a customized diet was designed for each participant, and adherence to these recommendations was high, with the exception of participant number 11, who was diagnosed with anorexia nervosa.…”
Section: Resultsmentioning
confidence: 99%
“…In HD, it was reported that antioxidants may exert beneficial effects, promoting the functional neurogenesis. Specifically, dietary polyphenols ameliorated anxiety and depression via regulation of adult hippocampal neurogenesis, while flavanoids protected hippocampal neurons from oxidative stress …”
Section: Methodsmentioning
confidence: 99%
“…Several lines of evidence indicate that OS plays a critical role in psychiatric disorders (Hassan et al, ; Moniczewski et al, ; Ng, Berk, Dean, & Bush, ; Salim, ; Smaga et al, ; Tsaluchidu, Cocchi, Tonello, & Puri, ). Indeed, OS contributes to impaired adult hippocampal neurogenesis in HD (Velusamy et al, ) and antioxidants have been proposed to promote adult neurogenesis in HD (Velusamy et al, ).…”
Section: Oxidative Stress and Mitochondria Dysfunction In Hdmentioning
confidence: 99%
“…Anti-inflammatory action of RSV has shown to prevent lipopolysaccharide (LPS, a TLR4 ligand)-induced activation of murine RAW 264.7 macrophages and microglial BV-2 cells. RSV treatment has been reported to prevent pro-inflammatory effect of Aβ on macrophages by inhibiting activation of STAT1, STAT3 and NFκB activation by interfering with IKK and IκB phosphorylation (78). In addition, oral administration of RSV in a mouse model of cerebral amyloid deposition significantly reduced microglial activation related to amyloid deposition.…”
Section: Role Of Rsv In Attenuating Aβ Mediated Toxicitymentioning
confidence: 99%